Percepción de los docentes sobre la implementación del constructivismo en la práctica pedagógica - Camargo Cuéllar, Mónika (2023)
The study arises as a need to know the conceptions of constructivism in RBE. The constructivist paradigm understands knowledge as a mental and subjective construction of the subject who learns, who in his active role interprets reality from his previous knowledge and cognitive conflict. The teacher is understood as a mediating agent of the process that provides the scaffolding that promotes the development of learning. Therefore, part of the research question: What are the perceptions of teachers of a private institution in Lima on the implementation of constructivism in pedagogical practice? The objective is to analyze the perceptions of primary school teachers on the implementation of constructivism in pedagogical practice. The study is assumed under a qualitative approach on a descriptive level. The informants are primary school teachers selected with the inclusion and exclusion criteria. Semi-structured interviews and documentary analysis were applied. The results show that teachers have information regarding constructivism, but present certain gaps of constructivism for planning and implementation. As outstanding conclusions, it can be mentioned that there is still a presence of traditional practices, it is also pointed out that what was learned in the initial training provided bases for pedagogical practice but that through continuous training teachers can understand and apply new educational approaches.